A micro-synthetic jet in a microchannel using bubble growth and collapse. (September 2019) - Sourtiji, Ehsan; Peles, Yoav
Highlights: An approach to generate synthetic jets at micro scale using bubble growth and collapse is introduced. The approach eliminates physical moving parts. Interfacial layer between vapor and liquid phases acts as a flexible membrane. Blinking thermal bubbles are generated using pulsating heat flux at different frequencies. An optimum operational value for the input power and frequency is studied. Abstract: A concept to power micro synthetic jets using bubble growth and collapse is introduced and studied over a range of operating frequencies (0.1–2.5 Hz) and heating powers (3–4.5 W). The microfluidic device has no moving parts and uses the interfacial layer between the vapor and liquid phases which substitutes the requirement for a physical flexible membrane. A micro heater inside a chamber (3.5 mm in radius and a height of 220 µm) was connected to a main microchannel through a nozzle with a 300 µm opening. Periodically powering the micro-heater triggered bubble explosion and implosion in the chamber, which in turn generated the synthetic jet. Sequential images of bubble nucleation, growth and collapse were captured using high-speed camera photography and a microscope. A momentum coefficient was used to characterize the synthetic jet. It was found that its average value exceeds unity for a large range of operating frequencies suggesting that this synthetic jet can improve the performance of a range of micro-system performance, such as micro-mixing in microfluidic devices.